Stablecoins and their risks to financial stability - Cameron MacDonald; Laura Zhao (Bank of Canada, 2022)
The market for fiat-referenced cryptoassets, commonly known as stablecoins, has expanded rapidly in recent years alongside the growth of the cryptoasset ecosystem. In fact, the market capitalization of stablecoins increased by more than 30 times since the beginning of 2020. What risks could stablecoins pose to the financial system? We examine price stabilization mechanisms of stablecoins as well as the current and potential use cases of stablecoins. We then analyze the risks stemming from both. We argue that the price stabilization mechanisms of current stablecoins could lead to the risk of confidence runs, which can propagate to broader cryptoasset markets and the traditional financial sector. We also argue that stablecoins can contribute to risks to financial stability by facilitating the buildup of leverage and liquidity mismatches in decentralized finance. Such risks cannot be addressed by regulating the safety and soundness of stablecoins alone without adequately regulating broader activities in the crypto ecosystem. Finally, we explore the potential implications of the substitution of cash and bank deposits for stablecoins in payments and the financial system more broadly, particularly the current system of bank-intermediated credit and for monetary policy.
Keywords: E42; E44; E58; G23; 330; Digital currencies and fintech; Financial markets; Financial stability; Financial institutions; Financial system regulation and policies